Changes in serum angiogenic factors among patients with acute pain and subacute pain - Yang, Xuewei; Yuan, Chunmei; Wang, Huanling; Wang, Yunxia; Liu, Mei; Li, Zongjin; Zhang, Jun (Frontiers in Molecular Neuroscience, 2022)
Screening serum biomarkers for acute and subacute pain is important for precise pain management. This study aimed to examine serum levels of angiogenic factors in patients with acute and subacute pain as potential biomarkers. Serum samples were collected from 12 healthy controls, 20 patients with postherpetic neuralgia (PHN), 4 with low back pain (LBP), and 1 with trigeminal neuralgia (TN). Pain intensity in these patients was evaluated using the visual analogue scale (VAS). The serum concentrations of 11 angiogenic biomarkers were examined by Milliplex Map Human Angiogenesis Magnetic Bead Panel 2. The pain assessment from VAS showed that all patients showed moderate and severe pain. Among 11 angiogenic factors, osteopontin (OPN), thrombospondin-2 (TSP-2), soluble platelet endothelial cell adhesion molecule-1(sPECAM-1), soluble urokinase-type plasminogen activator receptor (suPAR), and soluble epidermal growth factor receptors (sErbB2) were up-regulated and soluble interleukin-6 receptor α (sIL-6Rα) were down-regulated in patients with pain compared to the healthy participants (all P values were ＜0.005). Moreover, a linear regression model showed that the serum OPN concentration was correlated with pain intensity in patients with PHN (P = 0.03). There was no significant difference between the serum concentration of soluble epidermal growth factor receptors, sErbB3, soluble AXL, tenascin, and soluble neuropilin-1 in patients with acute and subacute pain and that of healthy controls. The results of this study provided new valuable insights into our understanding of angiogenic factors that may contribute to as mechanistic biomarkers of pain, and reveal the pathophysiological mechanism of pain.